Association of donor-specific antibodies with adverse outcomes in solid organ transplantation: A systematic review and meta-analysis of 69 studies - Kang, Zhong-yu; Han, Xue-ya; Liu, Chun; Liu, Wei; Li, Dai-hong (Frontiers in Immunology, 2025)
ImportancePreformed donor-specific antibodies (pre-DSAs) are a significant immunologic barrier in solid organ transplantation (SOT), yet their association with post-transplant outcomes lacks consensus, limiting standardized clinical management.ObjectiveTo determine the association between pre-DSA and posttransplant complications, including antibody-mediated rejection (AMR), T cell-mediated rejection (TCMR), graft loss, and patient mortality, with subgroup analyses stratified by organ type and MFI thresholds (1,000 cutoff).Data sourcesSystematic review of 3,322 studies from PubMed, Embase and the Cochrane Library (from inception to February 2024) following the PRISMA guidelines.Study selectionSixty-nine observational studies (22,737 transplant recipients; 3,787 pre-DSAs+), including retrospective and prospective cohorts, encompassing kidney (KT) (41 studies), liver (LT) (13), lung (6), heart (3), and other organ transplants.Main outcomes and measuresPrimary: AMR, TCMR, graft loss, patient death.Secondary: Biliary complications, bacteremia, delayed graft function (DGF).ResultsPre-DSAs positivity conferred significantly elevated risks of AMR (RR = 5.21, 95%CI 4.01–6.79), graft loss (RR = 2.11, 1.72–2.60), and mortality (RR = 1.62, 1.39–1.89) compared with pre-DSAs–negative recipients, with marked heterogeneity across organ types. KTs faced the highest risk of AMR risk (RR = 6.09, 4.39–8.46), whereas LT recipients exhibited elevated mortality (RR = 1.81, 1.30–2.53) but lower AMR rates (RR = 1.81 vs. KT). The thoracic organs (heart/lung) had no significant association with AMR (RR1.32, 0.86–2.03). Stratification by MFI thresholds revealed amplified risks at MFI≥1,000, particularly for AMR (RR = 7.51 vs 4.65 at MFI<1,000; Pinteraction<0.001) and loss of graft (RR = 2.30 vs 1.81; P = .032). KT with MFI≥1,000 had the highest cumulative hazards (AMR: RR = 8.12, 5.94–11.10; graft loss: RR = 2.55, 1.98-3.28), whereas LT recipients with MFI≥1,000 had higher mortality RR = 2.01 (1.44–2.80). Secondary outcomes included increased delayed graft function (DGF: RR = 1.49, 1.12–1.98) in pre-DSA+ patients, driven by KT (RR = 1.82, 1.30–2.55), but no association with T-cell–mediated rejection (TCMR: RR = 1.10, 0.94–1.28).ConclusionsPre-DSAs is a strong independent predictor of AMR and graft loss in SOT, with amplified risks in KT and cohorts with DSA+ MFI≥1,000. These findings advocate for universal pretransplant DSAs screening and DSA+MFI-guided desensitization to prioritize high-risk patients. Organ-specific strategies, intensified AMR surveillance in KTs, and mortality-focused monitoring in LTs, are critical to improving outcomes.